Degradation of organic molecules by tribovoltaic mechano-chemistry. (March 2023) - Lin, Leqi; Thyagaraja, Vashin Gautham Nanjangud; Ranjith, Renoy; Yang, Ruizhe; Ciampi, Simone; Chen, James; Liu, Jun
Abstract: The presence and accumulation of organic pollutants in water systems is a significant threat to the health of humans and aquatic ecosystems. Herein we demonstrate a new mechanism for high-efficient degradation of organic molecules based on the tribovoltaic effect. The method does not require photo-irradiation nor external power sources, but only use mechanical energy to generate electron-hole (e-h) pairs at dynamic metal-semiconductor contacts. Under short-circuit condition, e-h pairs in the heterojunction manifest themselves as direct-current (DC) output. Interacting with water under stirring or ultrasonication, the e-h pairs excited by collision between metal and semiconductor particles are capable of generating highly reactive free radicals and driving dye molecule degradation. Such mechano -catalysis mechanism is proved to be a versatile strategy with a broad range of material selection and mechanical stimuli, which has great implications for cost- and energy-effective water treatment, as well as potential applications in green chemical synthesis. Graphical Abstract: ga1 Highlights: Organic molecule reaction based on tribovoltaic effect in solid-liquid interface has been demonstrated. The mechanism of tribovoltaic effect-promoted free radical generation has been revealed. The new approach does not require photo-irradiation or external electric power. The mechanical stimuli can have different forms such as stirring and ultrasonication. Solar-mechanical co-treatment with the proposed mechanism has been demonstrated.